Early Diabetic Nephropathy and Retinopathy in Patients with Type 1 Diabetes Mellitus Attending Sudan Childhood Diabetes Centre - Hana Ahmed; Tayseer Elshaikh; Mohamed Abdullah (Journal of Diabetes Research)
Objective. Data on microvascular complications in children and adolescents with type 1 diabetes mellitus (T1DM) in Sudan are scarce. This study was aimed at determining the prevalence of diabetic nephropathy (DN) and retinopathy (DR) and their relationship to certain risk factors in children with T1DM attending the Sudan Childhood Diabetes Centre. Design and Methods. A clinic-based cross-sectional study of 100 patients with T1DM aged 10-18 years. Patients with disease duration exceeding 5 years if the onset of diabetes was prepubertal and 2 years if it was postpubertal were included. Relevant sociodemographic, clinical, and biochemical information was obtained. Blood pressure was measured. The patients were screened for DN and DR using urinary microalbumin estimation and fundus photography, respectively. Results. The frequency of microalbuminuria and diabetic retinopathy was 36% and 33%, respectively. Eleven percent had both retinopathy and microalbuminuria. Seven percent of the patients were found to be hypertensive. Patients with diabetic retinopathy had significantly higher HbA1c levels (p=0.009) and longer diabetes duration (p=0.02) than patients without retinopathy. Logistic regression showed that high HbA1c (odds ratio (OR) 0.83, confidence interval (CI) 0.68-1.00, p=0.04), but not age, duration, ethnic group, BMI, blood pressure, and presence of nephropathy, was an independent risk factor for retinopathy. Likewise, high blood pressure (OR 6.89, CI 1.17-40.52, p=0.03), but not age, duration, ethnic group, BMI, HbA1c, and presence of retinopathy, was a predictor for nephropathy. Conclusion. High prevalence of incipient DN and early stages of DR were observed in this study. Longer diabetes duration and higher HbA1c were associated with the presence of diabetic retinopathy. High blood pressure was a risk factor for DN. So regular screening for these complications and optimization of glycemic control are needed.